2022
DOI: 10.3390/bs12090329
|View full text |Cite
|
Sign up to set email alerts
|

Resilience, Stress, and Burnout Syndrome According to Study Hours in Spanish Public Education School Teacher Applicants: An Explanatory Model as a Function of Weekly Physical Activity Practice Time

Abstract: The selection process for the teaching profession in public elementary education is difficult, which can lead to the appearance of disruptive states in applicants. For this reason, the present study aimed to establish the relationship between study hours and the levels of stress, burnout, and resilience in applicants to the Spanish public teaching profession. Accordingly, this objective was achieved by (a) developing an explanatory model of study hours according to levels of stress, burnout, and resilience, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…A study in Brazil also reported that around a third of midwives had moderate job burnout [48]. The high level of job burnout in the emotional exhaustion dimension compared to other dimensions in the current study might be due to the high level of job stress, as stress has been found to be related to increased job burnout in the emotional exhaustion dimension in other studies [32,49,50]. Nevertheless, demographic factors did not play a signi cant role in the occurrence of STS in the present study.…”
Section: Discussionmentioning
confidence: 49%
“…A study in Brazil also reported that around a third of midwives had moderate job burnout [48]. The high level of job burnout in the emotional exhaustion dimension compared to other dimensions in the current study might be due to the high level of job stress, as stress has been found to be related to increased job burnout in the emotional exhaustion dimension in other studies [32,49,50]. Nevertheless, demographic factors did not play a signi cant role in the occurrence of STS in the present study.…”
Section: Discussionmentioning
confidence: 49%
“…This finding is in line with Stanley & Mettilda Buvaneswari's (2020) research findings revealed that stress levels negatively affect the manifestation of resilience. Recent research also supports a negative relationship between stress and resilience (Melguizo-Ibáñez et al, 2022).…”
Section: Discussionmentioning
confidence: 93%
“…It is characterized by a loss of motivation to work, physical fatigue or emotional exhaustion. This can have a negative impact on physical and mental health and lead to chronic fatigue or a lack of resilience [19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%